Tourism and coastal & maritime cultural heritage: a dual relation. Issue 6 (2nd November 2022) - Ferreira da Silva, Margarida; Vegas Macias, Jordi; Taylor, Steve; Ferguson, Laura; Sousa, Lisa P.; Lamers, Machiel; Flannery, Wesley; Martins, Filomena; Costa, Carlos; Pita, Cristina
ABSTRACT: Coastal and Maritime Cultural Heritage (CMCH) is an important asset in coastal areas. However, this heritage has been exposed to several environmental and human-created threats. This paper presents three European coastal regions with relevant CMCH and important tourism destinations: Ria de Aveiro (Portugal), the Small Isles (Scotland, UK) and Marsaxlokk (Malta). The paper draws attention to the challenges to CMCH they face, the dynamics between tourism and CMCH and provides recommendations for sustainable tourism exploitation of CMCH. A comparative case-study approach was undertaken, based on 41 semi-structured interviews with key stakeholders. Findings unveil that, despite the different demographics, socioeconomics and importance of tourism in each location, CMCH is seen as an important element to consider as tourism destination. Stakeholders identified economic, sociocultural and environmental dynamics between tourism and CMCH with positive and negative impacts on the regions. This study provides guidelines and recommendations that can be used as a reference to define a joint policy response for sustainable exploitation of CMCH in a tourism context.